КӘМЕЛЕТКЕ ТОЛМАҒАНДАРДЫҢ ҚЫЛМЫСТЫЛЫҒЫН АЛДЫН АЛУДЫ РЕТТЕЙТІН ҚАЗАҚСТАН РЕСПУБЛИКАСЫ ЗАҢНАМАСЫН ЖЕТІЛДІРУДІҢ КЕЙБІР МӘСЕЛЕЛЕРІ - Rakhmetov, Саттар Муканович; Abrayeva, Райхангуль Асановна (Scientific and legal journal «Bulletin of the Institute of Legislation and Legal Information of the Republic of Kazakhstan», 2014)
Author makes the proposals about changing norms of the draft Criminal Code envisaging the criminal responsibility for corruption offenses